Kokand Free Economic Zone - Zhobborov Azam Mashrabovich; Tojiboeva Mahliyo Azamzhon kizi; Karimov Shoulug Zokirjon ugli (Research Parks Publishers, 2022)
This scientific article provides important, interesting economic and geographical information about the Kokand Free Economic Zone, one of the important industrial centers that makes a significant contribution to the economic and social well-being of Uzbekistan, and the international economic zones in the world.